2014
DOI: 10.7124/bc.000889
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal and trophoblast immunophenotype of multipotent stromal cells from human placenta

Abstract: The investigation of trophoblast markers expression in the mesenchymal stromal cells of placental tissue before and after their isolation and cultivation. Methods. Placental multipotent mesenchymal stromal cells (MMSC) were obtained by culturing the adhesive fraction of cells enzymatically isolated from the placental tissue. The placental derived cells were immunophenotyped by flow cytometry and immunocytoche-mistry. Results. It was shown that the placental MMSC express the trophoblast markers: human chorionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…In the present study, rat and human PDMCs were characterized and it was demonstrated that they share similar surface immunophenotypes, with the exception of a lower expression of CD44 in rPDMCs. Furthermore, it has previously been demonstrated that hPDMCs express CD73 and CD105, but not CD34 or CD14 ( 40 ) and differentiated into osteogenic, adipogenic and chondrogenic lineages ( 41 ), thus fulfilling the minimal criteria for multipotent MSCs ( 42 ). Despite the absence of a classic mesenchymal surface immunophenotype ( 42 ), rPDMCs possessed the ability to differentiate into mesodermal cell lineages (adipogenic and osteogenic).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, rat and human PDMCs were characterized and it was demonstrated that they share similar surface immunophenotypes, with the exception of a lower expression of CD44 in rPDMCs. Furthermore, it has previously been demonstrated that hPDMCs express CD73 and CD105, but not CD34 or CD14 ( 40 ) and differentiated into osteogenic, adipogenic and chondrogenic lineages ( 41 ), thus fulfilling the minimal criteria for multipotent MSCs ( 42 ). Despite the absence of a classic mesenchymal surface immunophenotype ( 42 ), rPDMCs possessed the ability to differentiate into mesodermal cell lineages (adipogenic and osteogenic).…”
Section: Discussionmentioning
confidence: 99%
“…Various sources of obtaining human MSCs are indicated in the literature [61][62][63][64][65]. MSCs obtained from adipose tissue are the most studied [11], although stem cells of other origins are also used.…”
Section: Table 1 Examples Of Experimental Wound Healing Activity Stud...mentioning
confidence: 99%
“…MSCs obtained from adipose tissue are the most studied [11], although stem cells of other origins are also used. A new perspective source of MSCs is human placental tissue [58,[61][62][63]. In general, the positive effect of preparations with the inclusion of MSCs and their secretomes of various origins on the healing of skin lesions, including burn wounds, has been shown.…”
Section: Table 1 Examples Of Experimental Wound Healing Activity Stud...mentioning
confidence: 99%
“…Зараз з'являються відомості, що МСК не обов'язково повинні бути позитивними за маркером CD90 [25]. Показано наявність двох популяцій клітин С90+ і CD90-серед мультипотентних мезенхімальних стовбурових клітин плаценти [26]. У 99,6 % випадків клітини були одночасно негативні за маркерами CD45 i CD34.…”
Section: матеріали і методиunclassified